PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS THEORY OF DIDACTICAL SITUATION DALAM MATERI STATISTIKA - Putri Amara; Rafiq Zulkarnaen (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The aim of this study is to develop student worksheets in statistical material based on the theory of didactical situations. The theory of didactical situations was initiated by Brousseau to design learning situations based on a-didactic, milieu, and didactic situations. Model of Plomp’s design research is used to develop student worksheets, consisting of preliminary analysis (curriculum analysis, student learning trajectory, and statistical material analysis), stages of development, and prototype testing (self-revision, expert-review, one-to-one, and small-group tests). In the preliminary stage, interviews were conducted with one teacher and two students, obtaining didactic and epistemological obstacle on statistical material. The didactic and epistemological obstacles gained from interviews became epistemological models in composing the student worksheets. In the self-revision stage, the student worksheets are improved on aspects of language and material conformity. Meanwhile, the assessment of two experts recommends the student worksheets needs to improve the a-didactical situation. At the one-on-one stage to test the readability of the student worksheets tested to five students, in this stage, there is no improvement. Then, in the small group test stage tested to ten students and one teacher in the learning process obtained the conclusion of the student worksheets meets practicality and effectiveness. In general, the results obtained by the student worksheets have fulfilled practicality, effectiveness, and validity based on the theory of didactical situation that contains a didactic situation, milieu, and didactic situations.